The Development of Industrial Agglomeration in Industrial Designation Areas and its Impact on Land Use Change (Case Study: Pringsurat Subdistrict and Kranggan Subdistrict, Temanggung Regency) - Laila, Fadhilla Nur; Rahayu, Paramita; Widodo, Candraningratri Ekaputri (Desa-Kota: Jurnal Perencanaan Wilayah, Kota, dan Permukiman, 2024)
Industrial agglomeration refers to the clustering of industries in a specific region, where they are in close proximity and have interconnections. This phenomenon not only stimulates the growth of industrial activities, but also influences the development of other economic sectors. As industrialization expands, it gradually extends into rural areas that usually have abundant undeveloped land primarily used for agriculture. Consequently, this trend prompts a transition from agricultural to industrial land use. Pringsurat subdistrict and Kranggan subdistrict are located in Temanggung Regency, Central Java Province. Both of these subdistricts are designated as Industrial Designation Areas (KPI) according to the Temanggung Regency Spatial Plan 2011-2031. The plan has implications for the rapid development of large and medium industries. The purpose of this study is to examine the growth of industrial agglomeration in Pringsurat subdistrict and Kranggan subdistrict and their impact on agricultural land conversion. This research was conducted from 2023 to 2024 and utilizing data from 2021 and 2022. The approach of this research is descriptive quantitative and utilizes spatial analysis with Geographic Information Systems (GIS) and descriptive analysis techniques. Based on the results of the analysis, there is an agglomeration of large and medium industries in Pringsurat subdistrict and Kranggan subdistrict. The growth of agglomeration encourages the establishment of new industries and industry linkages. Furthermore, agglomeration growth has led to changes in land use, an increase in the variety of land uses, and an increase in land prices. Results of the analysis also show that there are regulatory changes in the development of industrial agglomeration that will affect to local government decision in the future.